1995
DOI: 10.1161/01.cir.91.4.999
|View full text |Cite|
|
Sign up to set email alerts
|

Depression and 18-Month Prognosis After Myocardial Infarction

Abstract: Depression while in the hospital after an MI is a significant predictor of 18-month post-MI cardiac mortality. Depression also significantly improves a risk-stratification model based on traditional post-MI risks, including previous MI, Killip class, and PVCs. Furthermore, the risk associated with depression is greatest among patients with > or = 10 PVCs per hour. This result is compatible with the literature suggesting an arrhythmic mechanism as the link between psychological factors and sudden cardiac death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
321
2
22

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,363 publications
(356 citation statements)
references
References 21 publications
11
321
2
22
Order By: Relevance
“…depression, anxiety or anger) has been associated with increased mortality in patients with [1,2,3] and without coronary artery disease (CAD) [4, 5], and this appears to be independent of biological risk factors. Most recently, the INTERHEART study estimated an attributable risk of 33% for combined psychosocial factors to acute myocardial infarction [6].…”
Section: Introductionmentioning
confidence: 99%
“…depression, anxiety or anger) has been associated with increased mortality in patients with [1,2,3] and without coronary artery disease (CAD) [4, 5], and this appears to be independent of biological risk factors. Most recently, the INTERHEART study estimated an attributable risk of 33% for combined psychosocial factors to acute myocardial infarction [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several prognostic studies have shown that depression is a predictor for survival after myocardial infarction [4,5,6,7] and the risk is directly related to the severity of depression: a 1- to 2-fold increase in CHD for minor depression and a 3- to 5-fold increase for major depression [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…27,29,30,49,92,251 There is also a well-recognised bidirectional association between the severity of physical illness and depression. 252 Living alone is linked both to an increased risk of depression in people with LTCs 253 and to worse outcome, 254 and life stressors are also associated with an increased risk of depression in elderly people. 255 All the factors in the model have an independent influence on unscheduled care use, but there are also multiple interactions between different components of the model, which may worsen overall outcome.…”
Section: Longitudinal Prospective Study To Determine Predictors Of Unmentioning
confidence: 99%